Nutrional Management in Chronic Kidney Disease Patients: Manajemen Gizi pada Pasien Chronic Kidney Disease (CKD) - Al Farisi, Ahmad Fathin; Kurniati, Intanri; Hadibrata, Exsa (Medula, 2024)
Chronic Kidney Disease (CKD) is kidney function disorder for >3 months. CKD is also a concern because of its relatively high prevalence and is one of the most common causes of death in Indonesia. A number of treatments that can be carried out in CKD patients depend on the symptoms, comorbidities, and complications in the patient. Management of CKD patients can be medical, operative, to conservative. Assessment of nutritional status is also a concern in patients with CKD because it is not uncommon for a decrease in nutritional status to occur. CKD patients undergoing dialysis treatment are more prone to experience protein-energy wasting (PEW). There are a number of nutritional therapies that can be performed on CKD patients, namely a low-protein diet, regulation of energy intake, oral supplementation, and IPPN/IPAA